2015
DOI: 10.1007/s00063-015-0070-7
|View full text |Cite
|
Sign up to set email alerts
|

Nicht indizierte Aufnahmen auf der Intensivstation

Abstract: In this study, patients were regularly admitted to the ICU despite their contrary wish/directive or an unfavorable clinical condition. Although this was registered in only 1 % of all admissions, optimizing preICU admission information flow with regard to relevant exclusion criteria not only helps respect patient autonomy but also allows for more adequate resource allocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Similarly, a study in the UK found that 17.2% of ICU physicians would have admitted to the ICU a patient whose probability of survival was estimated to be less than 1% [10]. In their prospective, single-centre study from Germany, Bangert et al reported that among the 50 patients for whom the ICU admission was considered to be futile by interdisciplinary consensus, 82% had expressed (either directly, or in writing through advanced directives, or through a family member) the desire not to be admitted to intensive care [11], whereas the corresponding percentage in our study was 23%. Cultural differences between countries, including legislative aspects, could at least partially explain these conflicting findings [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study in the UK found that 17.2% of ICU physicians would have admitted to the ICU a patient whose probability of survival was estimated to be less than 1% [10]. In their prospective, single-centre study from Germany, Bangert et al reported that among the 50 patients for whom the ICU admission was considered to be futile by interdisciplinary consensus, 82% had expressed (either directly, or in writing through advanced directives, or through a family member) the desire not to be admitted to intensive care [11], whereas the corresponding percentage in our study was 23%. Cultural differences between countries, including legislative aspects, could at least partially explain these conflicting findings [12, 13].…”
Section: Discussionmentioning
confidence: 99%